PENGARUH KARAKTERISTIK PSIKOLOGIS, SIKAP BERWIRAUSAHA, DAN NORMA SUBYEKTIF TERHADAP NIAT BERWIRAUSAHA - Singgih Santoso; Budi Sutedjo Dharma Oetomo (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2016)
Entrepreneurship education is currently done in college, with the intention to form youth entrepreneur and succesful independent life; many factors thought to influence the formation of entrepreneurship intention to young people who have got entrepreneurship education. The research aims to test the research model that describes the relationship between psychological characteristics constructs, subjective norm constructs, attitudes to entrepreneurship constructs, and entrepreneurship intention constructs among the students who have got knowledge about entrepreneurship. Using survey by questionnaires distributing to more than one hundred and seventy students, research results showed that there are positive and significant relationship between Psychological Characteristics with Entrepreneurship Attitudes construct, and Entrepreneurship Attitudes constructs with Entrepreneurship Intention construct. There is another interesting research finding that there is no relationship between Subjective Norms cosntruct with any of Psychological Characteristics construct, Entrepreneurship Attitude construct, and Entrepreneurship Intention construct. This is presumably because the majority of respondents plan to work after graduation and after a while they just think of the possibilities for entrepreneurship activities.